MANAJEMEN PENGELOLAAN KELAS DALAM PROSES TUJUAN PEMBELAJARAN SISWA DI SDN 09 SUNGAI KELAMBUTAHUN PELAJARAN 2023-2024 - Khairul Rozikin; Aslan Aslan; Rona Rona (CV. ADIBA AISHA AMIRA, 2025)
This journal aims to obtain complete and in-depth information about Classroom Management in Student Learning Objectives at SDN 09 Sungai Kelambu in the 2023-2024 Academic Year. This study uses a qualitative approach with a descriptive research type. Data collection techniques in this study use interview, observation and documentation techniques. Data analysis techniques used are data collection, data reduction, data presentation and drawing conclusions. Data validity checking techniques use triangulation and member check. The results of the study show that: (1) Teachers in classroom management to achieve learning objectives, namely teachers create an orderly atmosphere and regulate behavior, including making a picket schedule, and teachers reprimand students who violate school rules (2) The form of management to discipline students is the teacher using U formation, groups and traditional formations during the learning process